Digging out another cryptic species: A new sand frog (Anura: Pyxicephalidae: Tomopterna) from Mozambique - Channing, Alan; Pietersen, Darren W.; Dawood, Abeda (Zootaxa, 2025)
A new species of Tomopterna is described from Banhine National Park, southern Mozambique. It differs from all other sand frogs by an uncorrected p-distance of 4.9–8.7% for 16S rRNA. The new species can be distinguished from all other described species of sand frogs by: males 37 mm SVL or less, undivided subarticular tubercles, more than three phalanges free of webbing on the fourth toe, a continuous glandular ridge below the tympanum, a distinct tympanic membrane, the nostrils closer to the snout tip than the eye, the rounded canthus rostralis, a round tympanum, the absence of an outer metatarsal tubercle, an interrupted inter-orbital bar, small dorsal warts, the absence (or weakness) of vomerine teeth, the solid pigmented throat in mature males, the distinct palmar tubercles, the smooth ventral surface, and barring on the limbs. This description adds a further amphibian to the list of Mozambican frogs, which has increased significantly in recent years.